2000
DOI: 10.1021/ma9917702
|View full text |Cite
|
Sign up to set email alerts
|

Combined Gelatin−Chondroitin Sulfate Hydrogels for Controlled Release of Cationic Antibacterial Proteins

Abstract: Chemically cross-linked gelatin−chondroitin sulfate (ChS) hydrogels were prepared for the controlled release of small cationic proteins. The amount of chondroitin sulfate in the gelatin gels varied between 0 and 20 wt %. The chemical cross-link density, the degree of swelling, and the rheological behavior were determined to characterize the cross-linked hydrogels. Chemically cross-linked gelatin−ChS hydrogels were loaded with lysozyme, and the release was measured using phosphate-buffered saline. The lysozyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…[90] Chemically crosslinked gels are formed either by reactions between activated functional groups of polymer chains or by using small molecular weight crosslinkers, by triggering the reactions by photosensitive agents or by initiation with an enzyme. [91,92] …”
Section: Chemically Crosslinked Hydrogelsmentioning
confidence: 99%
“…[90] Chemically crosslinked gels are formed either by reactions between activated functional groups of polymer chains or by using small molecular weight crosslinkers, by triggering the reactions by photosensitive agents or by initiation with an enzyme. [91,92] …”
Section: Chemically Crosslinked Hydrogelsmentioning
confidence: 99%
“…CS was incorporated as the final layer, which was confirmed by the morphological change into thick mesh-like structures with distinct networks. The negatively charged carboxylate and sulfate groups present in CS allows for electrostatic interactions with free NH3 + groups of Ch thereby promoting attachment to the FVC-DSp-Col-I-Ch matrices [93]. Additionally GAGs with high charge density such as CS have been shown to interact well with collagen and multiple interactions can be facilitated through CS chains [94].…”
Section: Development Of Scaffoldsmentioning
confidence: 99%
“…Additionally, the diffusion was more hindered in hydrogels with higher dextran concentrations. Another example are gelatin hydrogels in which chondroitin sulfate (ChS) was incorporated to retard the release of cationic proteins because of electrostatic interactions (51). FRAP showed that diffusion of lysozymes inside the hydrogel increases with increasing ChS content.…”
Section: Diffusion Inside Hydrogelsmentioning
confidence: 99%